Indigenous health and well-being in the COVID-19 pandemic
1 online resource (xii, 256 pages)
Keywords: "This book investigates the impact of the COVID-19 pandemic on the health and well-being of Indigenous Peoples and assesses the policy responses taken by governments and Indigenous communities across the world. Bringing together innovative research and policy insights from a range of disciplines, this book investigates the impact of the COVID-19 pandemic on the health and well-being of Indigenous Peoples across the world, with coverage of North America, Central America, Africa, and Oceania. Further, it explores the actions taken by governments and Indigenous communities in addressing the challenges posed by this public health crisis. The book emphasises the social determinants of health and well-being, reflecting on issues such as self-governance, human rights law, housing, socioeconomic conditions, access to health care, culture, environmental deprivation, and resource extraction. Chapters also highlight the resilience and agency of Indigenous Peoples in combating the COVID-19 pandemic, despite the legacy of colonialism, patterns of systemic discrimination, and social exclusion. Providing concrete pathways for improving the conditions of Indigenous Peoples in the wake of the COVID-19 pandemic, this book is essential reading for researchers across indigenous studies, public health, and social policy"--